2022
DOI: 10.1186/s40359-022-00887-5
|View full text |Cite
|
Sign up to set email alerts
|

Intervention outcome preferences for youth who are out of work and out of school: a qualitative study

Abstract: Background While interventions have been developed and tested to help youth who have become disconnected from work and school, there is a paucity of research on young people’s intervention preferences. This study aims to understand young people’s preferred intervention outcomes and approaches for youth who are out of work and school. Methods Thirty youth participated in virtual focus groups. Transcripts were analyzed using thematic analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Second, NEY emphasized that encounters with the workplace provided by participating NGOs were limited in type and prevented them from fully exploring their career interests and finding their fit with specific jobs. Their emphasis on career interests and an in-depth understanding of the business world was consistent with what Zhu et al (2022) also found. For that reason, future implementations of the HKBM (Community) should consider expanding the existing types of business partners involved.…”
Section: Discussionsupporting
confidence: 82%
“…Second, NEY emphasized that encounters with the workplace provided by participating NGOs were limited in type and prevented them from fully exploring their career interests and finding their fit with specific jobs. Their emphasis on career interests and an in-depth understanding of the business world was consistent with what Zhu et al (2022) also found. For that reason, future implementations of the HKBM (Community) should consider expanding the existing types of business partners involved.…”
Section: Discussionsupporting
confidence: 82%
“…An initial set of six attributes with three to four levels was developed from the literature review, highlighting components such as mental health, goals, and skills training. Second, focus groups were conducted among youth (16–29 years) with Upcoming and at-risk Upcoming status across Canada to obtain youth feedback on proposed service outcomes [ 39 ]. Thematic analysis [ 40 ] of the focus group data identified prominent attributes and levels, including skills training, mentorship, and networking.…”
Section: Methodsmentioning
confidence: 99%
“…An initial set of six attributes with three to four levels was developed from the literature review, highlighting components such as mental health, goals, and skills training. Second, focus groups were conducted among youth (16-29 years) with Upcoming and at-risk Upcoming status across Canada to obtain youth feedback on proposed service outcomes (37). Thematic analysis (38) of the focus group data identi ed prominent attributes and levels, including skills training, mentorship, and networking.…”
Section: Discrete Choice Experiments (Dce)mentioning
confidence: 99%